2017
DOI: 10.1101/104620
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identifying the abundant and active microorganisms common to full-scale anaerobic digesters

Abstract: Anaerobic digestion is widely applied to treat organic waste at wastewater treatment plants. Characterisation of the underlying microbiology represents a source of information to develop strategies for improved operation. To this end, we investigated the microbial community composition of thirtytwo full-scale digesters over a six-year period using 16S rRNA gene amplicon sequencing. Sampling of the sludge fed into these systems revealed that several of the most abundant populations were likely inactive and immi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 55 publications
3
16
0
Order By: Relevance
“…[28]. This assumed metabolic potential has also been suggested in other studies that analyzed the microbial diversity in mesophilic anaerobic digesters [29,30]. Finally, the well described acetoclastic methanogenic capacity of the Methanosaeta genus could be attributed to the high SMA values determined in Periods 4 and 5.…”
Section: Resultssupporting
confidence: 68%
“…[28]. This assumed metabolic potential has also been suggested in other studies that analyzed the microbial diversity in mesophilic anaerobic digesters [29,30]. Finally, the well described acetoclastic methanogenic capacity of the Methanosaeta genus could be attributed to the high SMA values determined in Periods 4 and 5.…”
Section: Resultssupporting
confidence: 68%
“…Recently, through the use of 16S ribosomal RNA (rRNA) gene high-throughput amplicon sequencing and/or metagenomics, a number of studies have attempted to explore the microbial community ecology of AD, e.g. [ 3 , 8 14 ]. Although these studies have provided great insights into the structure, dynamics and functionality of microbial communities, most of them were limited to the municipal/industrial wastewater installations or farm reactors where animal manure and/or energy crops were the main feeding substrates.…”
Section: Introductionmentioning
confidence: 99%
“…viral predation [ 20 ], a stable core community composed of roughly 63 abundant genus-level operational taxonomic units (OTUs), accounting for 68% of relative community abundance, has recently been reported for activated sludge ecosystem [ 21 ]. Six-year monitoring survey of 32 Danish full-scale AD reactors also showed that out of the huge diversity of microbes merely 300 OTUs represented 80% of total rRNA reads across reactors [ 8 ]. While, the high overall diversity of microbes reported in different studies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…thermophilic anaerobic digesters. Amplicon abundance values (V1-3 region) are given as a percentage of total bacterial reads for the influent wastewater, activated sludge and anaerobic digester communities (19). *Novel MiDAS genus level taxa are given in bold.
Figure 3.Box plot for the distribution of the 10 most abundant archaeal genus-level-taxa by median abundance in A .
…”
Section: Curation and Expansion Of The Midas Taxonomymentioning
confidence: 99%
“…Sequences for all datasets (19) are classified with the MiDAS taxonomy v. 2.1.aSequences from all plants.bGenus level taxa not included in the base SILVA 123 taxonomy.…”
Section: Curation and Expansion Of The Midas Taxonomymentioning
confidence: 99%